Propofol Sedation During Spinal Anaesthesia - A Dose Finding Study - Ghimire, A; Bhattarai, B; Rahman, T R; Singh, S N; Koirala, S; Tripathi, M (Kathmandu University Medical Journal, 2012)
Background It is important to be able to measure and maintain a specific sedation level to compare outcomes of different levels of sedation during anesthesia and the aims include general patient comfort, freedom from specific discomfort, and some amnesia for both the block procedure and the surgical operation, in order to meet the patient’s preference and safety. In this prospective randomized clinical study, we compared the three different infusion doses of propofol. Objective To find out the appropriate infusion dose of propofol for optimal sedation without causing undue side effects in patients undergoing spinal anaesthesia. Method One hundred twenty patients ASA PS I-II were randomly allocated to three groups 1, 2 and 3 receiving propofol infusion at the rate of 25, 50 and 75 microgram/kg/min with concentration of (0.5%), (1%) and (1.5%) respectively. They were observed for sedation score, hemodynamic parameters and satisfaction level. The adverse effects like respiratory depression, nausea and vomiting score were assessed. Result Median sedation score increased in a dose dependent manner, with significantly higher scores in group 2 and 3 compared with group 1. Hemodynamic parameters were better in group 1 and 2 as judged by mephentermine requirement. The awakening time after stoppage of infusion was significantly delayed in group 3 (p < 0.001). Respiratory depression, nausea and vomiting were comparable clinically. Almost three fourth of the patients were satisfied with the techniques used. Conclusion Propofol infusion at the rate of 50mcg/kg/min for sedation in spinal anaesthesia provides optimal sedation, early awakening and excellent satisfaction level in the postoperative period. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6299 Kathmandu Univ Med J 2011;9(3):170-3